Dualisme Peradilan Militer dan Peradilan Umum: Problematika dan Urgensi Reformasi (The Dualism Of Military And Civilian Courts: Issues And The Urgency Of Reform) - Rahayu, Cantika Tresna; Triadi, Irwan (Media Hukum Indonesia (MHI), 2025)
The dualism between military courts and general courts in Indonesia presents a serious issue within the legal system, especially regarding the administration of justice for military personnel who commit general criminal offenses. Military courts still hold the authority to try soldiers for crimes committed outside of official duties, creating a potential space for impunity and human rights violations. This research aims to examine the problems caused by this jurisdictional dualism and explore the urgency of reforming the military justice system in Indonesia. This study uses normative legal research methods with a statutory approach, conceptual approach, and case study approach. The findings indicate that the authority of military courts to handle general crimes contradicts the principle of equality before the law and the spirit of legal reform. The Constitutional Court Decision No. 106/PUU-X/2012 serves as a critical foundation in pushing for military justice reform. Therefore, revising Law Number 31 of 1997 is urgently needed to ensure justice, transparency, and accountability within Indonesia’s judicial system